Clinical practice and research progress of Traditional Chinese Medicine nursing of neurogenic cervical spondylosis (神经根型颈椎病中医护理干预及研究进展) - WANG Yan (王岩); TANG Shiming (唐世明); ZHANG Lin (张林); DING Shengnan (丁圣楠); CHEN Qi (陈奇) (Association of Integrative Nursing, 2023)
With changes in lifestyle, the incidence of cervical spondylosis is developing at an increasing rate year by year, with the highest incidence being neurogenic cervical spondylosis, which has a great impact on patients' physical, psychological and quality of life. Traditional Chinese Medicine (TCM) nursing techniques have unique advantages over basic nursing operations, such as fewer side effects and higher comfort, and are therefore widely used in the treatment of neurogenic cervical spondylosis, which is the focus of current research and a hot spot. This article reviews the basic concept of neurogenic cervical spondylosis and the clinical practice and research progress of TCM nursing for it. It outlines the current clinical TCM nursing practices applicable to neurogenic cervical spondylosis, their application methods, scope of application and limitations, and aims to provide reference for the formulation and implementation of effective TCM nursing care for patients with neurogenic cervical spondylosis. (神经根型颈椎病严重影响患者的身体、心理和生活质量。中医护理操作具有操作简便、不良反应少、舒适度高等优势, 广泛应用于治疗神经根型颈椎病。本研究就神经根型颈椎病的基础概念及中医护理干预及研究进展进行综述, 概括目前临床适用于神经根型颈椎病的中医护理操作及其应用方法、适用范围及局限性, 旨在为神经根型颈椎病患者制定并实施有效的中医护理提供参考。)